Light scattering by subwavelength Cu2O particles. (27th February 2017) - Ullah, Kaleem; Liu, Xuefeng; Yadav, N P; Habib, Muhammad; Song, Li; García-Cámara, Braulio
Abstract: Novel metamaterials with new capabilities to manipulate light may be used by considering basic building blocks with new optical properties. This is the case with resonant magneto-dielectric particles. In this work, the resonant response of a high-dielectric Cu2 O subwavelength particle is analyzed, both analytically and experimentally. The emergence of electric and magnetic resonances and their interferential effects, producing directional behaviors, can be used in a new generation of metamaterials, as well as new integrated optical devices.